Microglia in Ischemic Stroke: Pathogenesis Insights and Therapeutic Challenges - Shui X; Chen J; Fu Z; Zhu H; Tao H; Li Z (Dove Medical Press, 2024)
Xinyao Shui,1,* Jingsong Chen,2- 4,* Ziyue Fu,1 Haoyue Zhu,1 Hualin Tao,2- 4 Zhaoyinqian Li2- 4 1Clinical Medical College, Southwest Medical University, Luzhou, People's Republic of China; 2Department of Laboratory Medicine, the Affiliated Hospital of Southwest Medical University, Luzhou, People's Republic of China; 3Sichuan Province Engineering Technology Research Center of Molecular Diagnosis of Clinical Diseases, Luzhou, People's Republic of China; 4Molecular Diagnosis of Clinical Diseases Key Laboratory of Luzhou, Luzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhaoyinqian Li, Department of Laboratory Medicine, the Affiliated Hospital of Southwest Medical University, No. 25, Taiping Street, Jiangyang District, Luzhou, Sichuan, 646000, People's Republic of China, Email lizhaoyinqian@swmu.edu.cnAbstract: Ischemic stroke is the most common type of stroke, which is the main cause of death and disability on a global scale. As the primary immune cells in the brain that are crucial for preserving homeostasis of the central nervous system microenvironment, microglia have been found to exhibit dual or even multiple effects at different stages of ischemic stroke. The anti-inflammatory polarization of microglia and release of neurotrophic factors may provide benefits by promoting neurological recovery at the lesion in the early phase after ischemic stroke. However, the pro-inflammatory polarization of microglia and secretion of inflammatory factors in the later phase of injury may exacerbate the ischemic lesion, suggesting the therapeutic potential of modulating the balance of microglial polarization to predispose them to anti-inflammatory transformation in ischemic stroke. Microglia-mediated signaling crosstalk with other cells may also be key to improving functional outcomes following ischemic stroke. Thus, this review provides an overview of microglial functions and responses under physiological and ischemic stroke conditions, including microglial activation, polarization, and interactions with other cells. We focus on approaches that promote anti-inflammatory polarization of microglia, inhibit microglial activation, and enhance beneficial cell-to-cell interactions. These targets may hold promise for the creation of innovative therapeutic strategies.Keywords: microglia, ischemic stroke, phagocytosis, polarization, crosstalk, anti-inflammatory, therapeutic targets